2017
DOI: 10.1093/sleep/zsx071
|View full text |Cite
|
Sign up to set email alerts
|

Prodromal Parkinsonism and Neurodegenerative Risk Stratification in REM Sleep Behavior Disorder

Abstract: ObjectivesRapid eye movement (REM) sleep behavior disorder (RBD) is the most specific marker of prodromal alpha-synucleinopathies. We sought to delineate the baseline clinical characteristics of RBD and evaluate risk stratification models.MethodsClinical assessments were performed in 171 RBD, 296 control, and 119 untreated Parkinson’s (PD) participants. Putative risk measures were assessed as predictors of prodromal neurodegeneration, and Movement Disorders Society (MDS) criteria for prodromal PD were applied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
136
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(145 citation statements)
references
References 40 publications
9
136
0
Order By: Relevance
“…One very recent large cross sectional study of 171 RBD patients found that 74% (95% CI 66, 80%) met Movement Disorders Society criteria for a diagnosis of prodromal Parkinson’s disease. 41 Longitudinal cohort studies of patients with idiopathic RBD have shown consistent evidence for a strong association with eventual phenoconversion to a defined neurodegenerative disease, predominantly the synucleinopathy phenotypes of PD, nonamnestic MCI, DLB, and MSA (Figure 3). 10,11,28,31,9397 Phenoconversion risk over 2 to 5 years is approximately 15% to 35%, and longitudinal follow-up between 12 and 25 years increases to 41% to 90.9%, although the risk of phenoconversion has substantial interindividual variability, sometimes occurring over 50 years after initial symptom onset.…”
Section: Clinical Implications Of Rbdmentioning
confidence: 93%
See 4 more Smart Citations
“…One very recent large cross sectional study of 171 RBD patients found that 74% (95% CI 66, 80%) met Movement Disorders Society criteria for a diagnosis of prodromal Parkinson’s disease. 41 Longitudinal cohort studies of patients with idiopathic RBD have shown consistent evidence for a strong association with eventual phenoconversion to a defined neurodegenerative disease, predominantly the synucleinopathy phenotypes of PD, nonamnestic MCI, DLB, and MSA (Figure 3). 10,11,28,31,9397 Phenoconversion risk over 2 to 5 years is approximately 15% to 35%, and longitudinal follow-up between 12 and 25 years increases to 41% to 90.9%, although the risk of phenoconversion has substantial interindividual variability, sometimes occurring over 50 years after initial symptom onset.…”
Section: Clinical Implications Of Rbdmentioning
confidence: 93%
“…Lastly, genetic studies of RBD remain limited, but RBD has been associated with glucocerebrosidase sequence variation and PD-related genetic loci including the microtubule associated protein tau ( MAPT ) gene in genome-wide association studies, 41,60,61 and the leucine rich repeat kinase ( LRRK2 ) mutation carriers with Parkinson disease. 41,62,63 It has been proposed that the variability in RBD expression in some genetic Parkinsonian disorders may reflect heterogeneous neuropathological substrate with less marked involvement of the brainstem REM atonia control structures in LRRK2 mutation carriers than in idiopathic PD.…”
Section: Pathophysiology Of Rbdmentioning
confidence: 99%
See 3 more Smart Citations